Sinus Bradycardia in an Adolescent Taking Lamotrigine - Davis, Genevieve; Ward, Kristen; Mohiuddin, Sarah (Case Reports in Psychiatry, 2022)
Lamotrigine is commonly prescribed for the treatment of neurological conditions and is increasingly being prescribed for psychiatric conditions as well. Although largely well tolerated, it is known to have a number of potential side effects, and in March 2021, the FDA issued its most recent warning for the medication due to its increased risk of cardiac arrhythmias. In this report, we describe a case in which an adolescent patient was found to be bradycardic after starting lamotrigine for antidepressant augmentation, with a gradual return to normal heart rate as the medication was subsequently tapered and discontinued. Further research is needed to more accurately estimate the risk of cardiac side effects and to establish appropriate monitoring guidelines for cardiac arrhythmias in those taking lamotrigine.